Intelligent computing and internet of things. Part II : first International Conference on Intelligent Manufacturing and Internet of Things and 5th International Conference on Computing and Sustainable Energy and Environment, IMIOT and ICSEE 2018, Chongqing, China, September 21-23, 2018 : proceedings - International Conference on Intelligent Manufacturing and Internet of Things 2018 : Chongqing, China); Li, Kang; Fei, Minrui; Du, Dajun; Yang, Zhile; Yang, Dongsheng; International Conference on Computing and Sustainable Energy and Environment 2018 : Chongqing, China) (Singapore : Springer, 2018)
The three-volume set CCIS 923, CCIS 924, and CCIS 925 constitutes the thoroughly refereed proceedings of the First International Conference on Intelligent Manufacturing and Internet of Things, and of the 5th International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2018, held in Chongqing, China, in September 2018. The 135 revised full papers presented were carefully reviewed and selected from over 385 submissions.The papers of this volume are organized in topical sections on: digital manufacturing; industrial product design; logistics, production and operation management; manufacturing material; manufacturing optimization; manufacturing process; mechanical transmission system; robotics.
Advanced evolutionary computing theory and algorithms -- Big data analytics -- Fault diagnosis and maintenance -- Intelligent computing in robotics -- Intelligent control and automation -- IoT systems -- Neural networks and deep learning -- Precision measurement and instrumentation -- Image processing.
International conference proceedings.
Includes author index.
Description based on online resource; title from digital title page (viewed on September 19, 2018).
Keywords: Artificial intelligence -- Industrial applications -- Congresses; Internet of things -- Congresses; Special Purpose and Application-Based Systems; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Artificial intelligence; Network hardware; Algorithms & data structures; Expert systems / knowledge-based systems; Computers -- Intelligence (AI) & Semantics; Computers -- Hardware -- Network Hardware; Computers -- Programming -- Algorithms; Computers -- Expert Systems; Artificial intelligence -- Industrial applications; Internet of things; Electronic books; Electronic books; Conference papers and proceedings